Kurikulum dan Pola Ilmu Pengetahuan Pada Masa Orde Lama dan Orde Baru - Lia Anitasari; Agung Cahyono (Social Science Academic, 2023)
This article aims to describe the history of the development of the Indonesian education curriculum during the Old Order, New Order and Reformation periods. Curriculum changes are made at least once every ten years. Because in the past ten years, it is very likely that there will be changes in various fields such as information communication technology and science. The method used in this research is historical as used in data collection techniques in library research. The object of study in this article focuses on tracing the history of curriculum development in Indonesia from the Old Order to the Reformation. The results of this study indicate that the curriculum in Indonesia has been developed twelve times, namely in 1947, 1952, 1964, 1968, 1973, 1975, 1984, 1994, 1999, 2004, 2006 and 2013. From this article it is hoped that it can educate the history of development existing curriculum in Indonesia.